Fortymile City, Alaska, ca. 1897. - La Roche, Frank (1892)
Caption on image: ""Forty Mile City, Alaska"" ""Forty Mile City, Alaska. In a recent report on the Yukon gold region, it says in relation to the Forty Mile gold district, that in the latter part of 1887, Franklin Gulch was struck, and $4,000 was an estimate of the amount of gold produced in the first year. Since then it has been a constant payer. The character of the gold discovered is of the nugget order and pieces to the value of $5.00 are frequently found. Forty Mile River joins the main river from the west. As far up as the international boundry line, about twenty-three miles, its course is southwest; thence it takes a more southerly direction. It is 100 to 150 yards wide at the mouth, and the current is generally strong with many small rapids."" (Frank La Roche, En Route to the Klondike, 1898) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number